Addison-Krise – Risiko erkennen und rasch behandeln - Meyer, Gesine; Badenhoop, Klaus (DMW - Deutsche Medizinische Wochenschrift, 2018)
An adrenal crisis (Addisonian crisis) is an acute life-threatening complication of adrenal insufficiency. It occurs when hydrocortisone demand is not met by supplementation in the context of an infection – often gastrointestinal, fever, trauma, acute psychological or physical stress. Symptoms of weakness, nausea, muscle/joint pain and drowsiness may develop out of robust health within few hours. If overlooked, treated too late, with insufficient dose or route of application, there exists a considerable risk of mortality. Treatment consists of immediate parenteral hydrocortisone (100 mg bolus) and subsequent continuous infusion until the underlying precipitating cause is cured and/or when regular supplementation can be continued. Physicians and nurses must not underestimate the condition, since diagnosis and treatment must not be delayed. Patients, relatives and spouses need to be trained in prevention and early recognition through educational programs and emergency cards.
Keywords: Nebenniereninsuffizienz; autoimmun polyglanduläres Syndrom; Kortisolmangel